Applications of Alginate-Based Nanomaterials in Enhancing the Therapeutic Effects of Bee Products - Al-Hatamleh, Mohammad A. I.; Alshaer, Walhan; Hatmal, Ma’mon M.; Lambuk, Lidawani; Ahmed, Naveed; Mustafa, Mohd Zulkifli; Low, Siew Chun; Jaafar, Juhana; Ferji, Khalid; Six, Jean-Luc; Uskoković, Vuk; Mohamud, Rohimah (Frontiers in Molecular Biosciences, 2022)
Since the ancient times, bee products (i.e., honey, propolis, pollen, bee venom, bee bread, and royal jelly) have been known as supernatural treatments that offer promising therapeutic effects against a wide range of diseases. This is due to the broad composition and chemical properties of bee products, regardless of the bee species, which has encouraged researchers to extensively study the therapeutic potentials of these products, especially honey. On the other hand, amid the unprecedented growth in nanotechnology research and applications, nanomaterials with various characteristics have been utilized to improve the therapeutic efficiency of these products. Towards keeping the bee products as natural and non-toxic therapeutics, the green synthesis of nanocarriers loaded with these products or their extracts has received a special attention. Alginate is naturally produced biopolymers from brown algae, with desirable properties that include biodegradability, biocompatibility, non-toxicity and non-immunogenicity. This review presents an overview of alginates, including their properties, nanoformulations, and pharmaceutical applications, placing a particular emphasis on their applications for the enhancement of the therapeutic effects of bee products. Despite the paucity of studies on fabrication of alginate-based nanomaterials loaded with bee products or their extracts, recent advances in the area of utilizing alginate-based nanomaterials and other types of materials to enhance the therapeutic potentials of bee products are summarized in this work. As the most widespread and well-studied bee products, honey and propolis have garnered a special interest; combining them with alginate-based nanomaterials has led to promising findings, especially for wound healing and skin tissue engineering. Also, future directions are proposed and discussed to help researchers in developing alginate-based bee product nanomedicines. In conclusion, since preserving original characteristics of the bee products is a crucial challenge in developing nano-carrier systems, alginate-based nanomaterials are well suited for this task because they can be fabricated without the use of harsh conditions, such as shear force and freeze-drying, which are often used for other nano-carriers. Further, conjunction of alginates with natural polymers such as honey not only combines the medicinal properties of the alginates themselves and honey but also could enhance the mechanical properties and cell adhesion capacity of alginates.